Estymacja indeksu ogona rozkładu stóp zwrotu na polskim rynku akcji - Pietrzyk, Radosław (Tail index estimation of returns distribution on Polish Stock Exchange, 2006)
In this paper a study on tail index estimation. Some data sets requiring heavy tailed models necessitates reliable methods of estimation a parameter governing the degree of tail heaviness In this paper three estimators Hill, Pickands and Dekkers- Einmahl-de Haan and the method of maximum likelihood estimation have been verified on Polish Stock Exchange.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 289-298